Post Cold Frontal Clouds at the ARM Eastern North Atlantic Site: An Examination of the Relationship Between Large‐Scale Environment and Low‐Level Cloud Properties. Issue 21 (5th November 2018) - Naud, Catherine M.; Booth, James F.; Lamraoui, Fayçal
Abstract: Using cloud and environment observations from the Atmospheric Radiation Measurement (ARM) program Eastern North Atlantic site and an automated cold front detection routine, cloud properties in post cold front (PCF) periods are examined and compared to similar conditions of subsidence (non‐PCF). PCF periods exhibit stronger subsidence and wind speed than non‐PCF periods, with weaker inversions and stronger surface temperature contrasts. Low‐level clouds are predominant and are found to have higher cloud base and top heights, colder cloud top temperature, and greater vertical extent and liquid water path during PCF than non‐PCF periods. The environmental metric that is best correlated with cloud boundaries for both PCF and non‐PCF periods is the difference in potential temperature between the sea surface and 800 hPa, a parameter used to locate cold air outbreak conditions. However, the cloud vertical extent and liquid water path are found to be better correlated with sea‐air temperature contrast, a parameter related to turbulent surface fluxes. The strength of the relationships between the cloud characteristics and these metrics does not differ for PCF and non‐PCF periods. However, the strength of the metrics differs between PCF and non‐PCF periods and can explain cloud property differences. The results suggest both the properties of the boundary layer and the presence of an upper‐level cyclone associated with the cold front determine PCF cloud properties. Key Points: Post cold frontal clouds at the ARM Eastern North Atlantic site are on average thicker, higher, and colder than clouds in non‐post cold front subsidence periods Weaker inversions and stronger surface temperature contrast help explain post cold frontal cloud characteristics Low‐level cloud boundaries are strongly correlated with the cold air outbreak parameter M in all subsidence periods at the ENA